Sources of ethnicity differences in non-cognitive development in children and adolescents - Ha Trong Nguyen; Luke Connelly; Huong Thu Le; Francis Mitrou; Catherine L. Taylor; Stephen R. Zubrick (ZBW – Leibniz Information Centre for Economics, 2019)
In most multi-cultural Anglo-Saxon countries, children of Asian immigrants have higher academic achievement than children of native-born parents. Yet, little is known about their relative non-cognitive performance. This study is the first to compare the non-cognitive skills of children of Asian immigrants and children of native-born Australian parents and seek to understand the evolution of non-cognitive skills. We find large differences in non-cognitive skill development between children of Asian immigrants and children of parents from other ethnicity groups. Furthermore, the nativity gaps in non-cognitive skills vary significantly by informants of non-cognitive skills, types of non-cognitive skills and children's ages. According to teacher ratings, children of Asian immigrants are found to excel in almost all non-cognitive attributes, particularly after school entry ages. By contrast, Asian immigrant parents rated their children lower in some selected non-cognitive attributes and at early ages. Adopting a cumulative value-added regression model and an Oaxaca-Blinder decomposition method, this paper shows differences in initial child non-cognitive abilities, parenting styles and children's time allocations are the most important factors explaining the ethnic non-cognitive skill gap. Moreover, ethnic differences in parenting styles and children's time allocations both contribute to reducing the ethnic gap in non-cognitive skills. By contrast, differences in other child or household characteristics explain very little of the ethnic non-cognitive skill gap.
Keywords: J13; J15; J22; J24; 330; Migration; Non-cognitive skills; Time Use Diary; Second-generation Immigrants; Australia